Vanuatu : 2018 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
Three years after Cyclone Pam struck Vanuatu causing extensive damages, reconstruction efforts are near completion with full recovery in sight. However, capacity constraints and coordination issues have hampered the use of committed funds by donors and development partners, thereby slowing down recovery. Meanwhile, the government's ambitious development agenda is making good progress with several major infrastructure projects completed or projected to be completed in the next year.